Perturbing integrin function inhibits microtubule growth from centrosomes, spindle assembly, and cytokinesis - Reverte, Carlos G. (The Rockefeller University Press, 2006)
In many mammalian cell types, integrin-mediated cell-matrix adhesion is required for the G1–S transition of the cell cycle. As cells approach mitosis, a dramatic remodeling of their cytoskeleton accompanies dynamic changes in matrix adhesion, suggesting a mechanistic link. However, the role of integrins in cell division remains mostly unexplored. Using two cellular systems, we demonstrate that a point mutation in the β1 cytoplasmic domain (β1 tail) known to decrease integrin activity supports entry into mitosis but inhibits the assembly of a radial microtubule array focused at the centrosome during interphase, the formation of a bipolar spindle at mitosis and cytokinesis. These events are restored by externally activating the mutant integrin with specific antibodies. This is the first demonstration that the integrin β1 tail can regulate centrosome function, the assembly of the mitotic spindle, and cytokinesis.